Faktor-Faktor yang Mempengaruhi Kesulitan Belajar Siswa dalam Mata Pelajaran Ekonomi di SMAN 01 Kota Bengkulu - Helmarini Helmarini; Piton Duwiki Saputera (Universitas Dehasen Bengkulu, 2022)
This study aims 1). to find out the factors that affect the difficulty of learning Social Science subjects Economics class X SMAN 01 Bengkulu city.2). to find out how much these factors affect student learning difficulties. The tool used is descriptive analysis to manage the factors, the results of the study found that the factors that influence student learning difficulties. Data collection techniques by means of observation, interviews, documentation. Based on the results of this study, it was found that the factors causing learning difficulties in Economics subjects were caused by the school environment and family environment, namely the school environment, the factor of inadequate educational facilities in schools, the way in which the subject matter was delivered by the teacher and the most dominant factor that became the learning difficulties of SMAN 01 Bengkulu city students is a way of delivering lesson material by the teacher.